1/f-noise-free optical sensing with an integrated heterodyne interferometer - Ming Jin (Nature Portfolio, 2021)
Suppressing 1/f-shaped low-frequency noise is critical but fundamentally challenging to both electrical and optical transducers. Here, the authors demonstrate a 1/f-noise-free optical sensor with integrated CMOS-compatible heterodyne interferometer and an upconversion amplifying technique, which suppresses the noise by two orders of magnitude.